Effect of degumming process on chromatographic separation of carotenes from crude and degummed palm oil - You, L.L.; Baharin, B.S.; Man, Y.B. Che; Takagi, S. (Wiley, 2001)
Carotene from crude palm oil (CPO) and degummed palm oil (DPO) was separated using synthetic polymer adsorption chromatography. Diaion HP-20 adsorbent was used for reverse-phase chromatography and column temperature was kept at 50C. Both 2-propanol and n-hexane were used as the first and the second eluting solvents, respectively. Phosphoric acid was used to remove the minor components in CPO in the degumming process. The turbidity of DPO was lower than that of CPO and the retention time in the column for DPO was shorter (21.3 min) compared to CPO (29 min) due to the removal of the minor components by phosphoric acid. Degumming process caused a reduction of 1.67 mg of total carotene content and 55.67 ppm of carotene concentration in CPO. This is probably due to the removal of carotenoids during the degumming process. After column chromatography, carotene recovery for CPO was 30.23% and 54.82% for the first and second fractions, respectively. On the other hand, carotene recovery for DPO was 33.91% for the first fraction and 46.25% for the second fraction. This indicated that the separation of carotene in CPO was more efficient than DPO in the column chromatography due to the longer retention time in the column. Under the process conditions investigated, carotene compositions were not affected by the degumming and column chromatography process.